1984
DOI: 10.1007/bf00304859
|View full text |Cite
|
Sign up to set email alerts
|

A histochemical and morphological study of skeletal muscle from obese hyperglycaemic ob/ob mice

Abstract: Summary. The histochemical and morphological charactefis= tics of muscles from lean and obese hyperglycaemic ob/ob mice were compared to determine the nature of the low skeletal muscle mass of the latter: Gastrocnemius and biceps brachii muscles from obese ob/ob mice were significantly lighter than those from lean mice; whereas the weights of soleus muscles were not significantly different. The small mass of the biceps brachii muscle resulted from a decrease in diameter of the large glycolytic fast white and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 30 publications
(39 reference statements)
5
22
0
Order By: Relevance
“…MSTN mRNA levels were also significantly increased in the TA but not the SOL muscle of ob/ob compared with wild-type mice, and in the TA muscle of mice on a high-fat diet compared with mice on a low-fat diet, whereas ActRIIb and FSTL3 mRNA levels were unchanged in either muscle. The higher MSTN mRNA levels are associated with a significantly lower TA muscle mass in ob/ob mice, whereas SOL mass was not significantly different, both of which have been previously reported (5). It is therefore tempting to speculate that the increase in MSTN expression is causally related to the decrease in muscle mass observed in the present study and the decrease in muscle mass and fiber size in ob/ob mice reported previously (5) by either initiating the atrophic cascade or maintaining muscle mass at its new smaller size.…”
Section: Discussionsupporting
confidence: 77%
“…MSTN mRNA levels were also significantly increased in the TA but not the SOL muscle of ob/ob compared with wild-type mice, and in the TA muscle of mice on a high-fat diet compared with mice on a low-fat diet, whereas ActRIIb and FSTL3 mRNA levels were unchanged in either muscle. The higher MSTN mRNA levels are associated with a significantly lower TA muscle mass in ob/ob mice, whereas SOL mass was not significantly different, both of which have been previously reported (5). It is therefore tempting to speculate that the increase in MSTN expression is causally related to the decrease in muscle mass observed in the present study and the decrease in muscle mass and fiber size in ob/ob mice reported previously (5) by either initiating the atrophic cascade or maintaining muscle mass at its new smaller size.…”
Section: Discussionsupporting
confidence: 77%
“…There is compelling evidence that the intramuscular fat content is higher in obese mammals, including rodents, 7,26 than in controls. This raises the possibility that the protein content in muscles from obese animals is lower than that in controls.…”
Section: Resultsmentioning
confidence: 99%
“…As all the three muscles examined were found to contain a greater proportion of hybrid fibres (a marker of structural remodelling 1 ), it is likely that this shift in the fibre type composition results from a process of structural remodelling associated with the obese condition rather than from a different developmental pattern followed by the muscles from the two animal groups. This contention is supported by data 7,42,43 I IIA IID I+IIA IIA+IIB IIA+IID IIB+IID I+IIA+IIB I+IIA+IID I+IIB+IID IIA+IIB+IID I+IIA+IIB+IID 0 10 Alterations in skeletal muscles of ob/ob mouse JG Kemp et al skeletal muscle phenotype in ob/ob mice do not appear until significant progression of obesity. The greater proportion of hybrid fibres detected in SM and EDL muscles of ob/ob mice, and the range of combinations of MHC isoforms co-expressed in these fibres, suggests a process of fibre type transition is taking place in the direction IIB-IID-IIA.…”
Section: Iiamentioning
confidence: 90%
See 1 more Smart Citation
“…Several abnormal characteristics of skeletal muscles in diabetic mouse are studied from morphological (Almond and Enser, 1984;Hamilton et al, 1968;Naccarato et al, 1970), chemical (Mayer et al, 1974) and electrophysiological aspects (Grossie, 1982). The male KK-CAy mouse has a genetically predisposed syndrome similar to human type II diabetes mellitus (NIDDM) and includes hyperglycemia, hyperinsulinemia, obesity, and insulin resistance (Kimura et al, 1979).…”
mentioning
confidence: 99%